THE REVIVAL OF MEDUSA IN TED HUGHES’S CHILDREN’S NOVELLA THE IRON WOMAN IN THE ECOFEMINIST CONTEXT - Ayyıldız, Nilay Erdem (My University, 2024)
British author and poet Ted Hughes’s The Iron Woman, a sequel to The Iron Man, is one of the children’s literature works awaiting to be discovered as a noteworthy ecofeminist work. The aim of this study is to explore the association between the Medusa myth and Hughes’s The Iron Woman, examining their shared roles as female resistance and empowerment within an ecofeminist context. Within the angle of gender, power dynamics and nature, the analysis reveals an innovative approach to the novella, which depicts how the imperishable mythological heroine Medusa is revived in an ecofeminist context. The study indicates how the heroines are similar to each other not only in terms of their physical features but also their insurgent natures and ways of punishing men to resist. In this regard, the study asserts that while evoking cultural awareness both for children and adults, The Iron Woman creates a reminiscent of Medusa in an ecofeminist manner. Therefore, the study sheds an ecofeminist light on the association between two female protagonists, examining the title character, the Iron Woman, as the revival of Medusa in a new context.
Keywords: Ecofeminism; Nature; Resistance; Medusa; The Iron Woman